A powder type cold drawn polymer coating agent and its preparation method and application
By using powdered polymer coating agents made of materials such as modified graphite and nano-silicon dioxide in the cold-drawing steel industry, the existing cold-drawing pre-treatment problems are solved, and environmental protection, strong adhesion, excellent lubricating performance and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411985625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
Smart Images

Figure BDA0005222516500000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating agents, and specifically discloses a powdery cold-drawn polymer coating agent and a preparation method and application thereof. Background Art
[0002] In the prior art, the wire rod needs to be pre-treated before cold drawing steel such as steel wire and steel strand. Considering the operating efficiency and steel pipe quality in the cold drawing process, the currently commonly used pre-treatment process is generally to pickle the tube blank to be cold drawn to remove the rust or self-oxide film on the surface, and then use electrolytic phosphating solution to pre-form a chemical coating of zinc phosphate on the surface of the tube blank, and then form a lubricating coating such as metal soap on the coating so that it can be smoothly drawn through the mold. Such pre-treatment can improve the corrosion resistance and wear resistance of the steel strand, while reducing friction damage during the process. During the cold drawing process, steel wire, steel strand and other steel can also achieve further improvement in strength and performance. However, this pre-treatment process involves a variety of chemical reagents, which is costly and also faces the problem of phosphating slag pollution.
[0003] The invention patent with the publication number CN113399483B discloses an environmentally friendly lubricating coating agent for cold-drawn steel wire and its preparation method and application. The coating agent includes a binder and a lubricant, wherein the binder accounts for 75-85% of the total amount; the binder is selected from one of anhydrous sodium silicate, sodium silicate monohydrate, sodium silicate dihydrate, sodium silicate pentahydrate, sodium silicate heptahydrate and sodium silicate nonahydrate, and the lubricant is composed of the following components: molybdenum disulfide and graphite, wherein the proportion of graphite is 85-95%. The invention overcomes the shortcomings of the prior art, replaces the phosphating solution, and completely innovates the pre-treatment process of the steel cold-drawn industry such as steel wire and steel strand, so that it can maintain an efficient production rate and save electricity, zero pollution and zero emissions in the pre-treatment process.
[0004] However, the lubricating properties of molybdenum disulfide and graphite as lubricants are limited, which may affect the comprehensive properties of cold-drawn steel products; and the adhesion performance of the coating agent may also be insufficient due to the moisture-sensitive nature of the silicate binder. Summary of the invention
[0005] In view of the defects of the prior art, the present invention discloses a powder-type cold-drawn polymer coating agent and its preparation method and application. The powder-type polymer coating agent provided by the present invention is environmentally friendly and has good adhesion, excellent lubrication performance and corrosion resistance, and is suitable for the application of various seamless steel pipes, wire rods, steel strands dry drawing and rolled steel pipe oil drawing.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] On the one hand, the present invention provides a powder type cold drawn polymer coating agent, which comprises the following raw materials in parts by weight: 2 to 5 parts of modified graphite, 1 to 3 parts of molybdenum disulfide, 2 to 10 parts of polyethylene glycol, 1 to 6 parts of silane coupling agent, 50 to 80 parts of acrylic resin, 1 to 5 parts of silicate, 1 to 2 parts of modified nano silicon dioxide, 1 to 10 parts of cross-linking agent and 1 to 3 parts of dispersant.
[0008] In some embodiments of the present invention, the preparation steps of the modified graphite are as follows:
[0009] The composite graphite is dispersed in an organic solvent by ultrasonic method, and then stearic acid is added. After the ultrasonic dispersion is continued for 1 to 2 hours, the organic solvent is removed by vacuum distillation to obtain the modified graphite.
[0010] In some embodiments of the present invention, the composite graphite is a mixture of natural flake graphite and spherical graphite.
[0011] Preferably, the mass ratio of the natural flake graphite to the spherical graphite is 1:(0.3-0.5).
[0012] Further preferably, the mass ratio of the natural flake graphite to the spherical graphite is 1:0.4.
[0013] In some embodiments of the present invention, the mass ratio of the composite graphite to stearic acid is 1:(0.1-0.3).
[0014] Preferably, the mass ratio of the composite graphite to stearic acid is 1:0.2.
[0015] In the prior art, graphite and molybdenum disulfide are often added as lubricants. When they are blended with polymer compounds, the surface energy of graphite and molybdenum disulfide affects the blending effect, which is not ideal. The present invention introduces stearic acid to modify the composite graphite, firstly reducing the agglomeration phenomenon that is easily caused by its surface energy, and increasing its compatibility in the system; at the same time, the applicant also found that the lubricity of the system is further increased. The possible reason is that the natural flake graphite and spherical graphite in the composite graphite undergo hydrogen bonding with the help of the hydroxyl groups remaining thereon, and then closely combine. When the introduced stearic acid has a certain coating effect on it, the exposure probability of the oxygen-containing groups that may still exist is reduced, and the dispersion stability of the composite graphite in the system is further improved; on the other hand, there may be a phenomenon similar to slip between the spherical graphite and the natural flake graphite, which further improves the lubrication performance of the system under the synergy of adsorption and friction with the molybdenum disulfide in the system.
[0016] In some embodiments of the present invention, the preparation steps of the modified nano-silica are as follows:
[0017] The nano-silica and deionized water are mixed, ultrasonically dispersed for 20 to 30 minutes, heated to 55 to 70° C., 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is added under stirring, and then acetic acid is added, and the temperature is continued to be raised to 70 to 80° C., stirred for reaction for 1 to 3 hours, and dried to obtain the modified nano-silica.
[0018] In some embodiments of the present invention, the mass ratio of the nano-silica to 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1:(0.3-0.5).
[0019] Preferably, the mass ratio of the nano-silicon dioxide to 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1:0.4.
[0020] In some embodiments of the present invention, the particle size of the nano-silicon dioxide is 10 to 30 nm.
[0021] The present invention modifies nano silicon dioxide. On the one hand, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane long chain segments are introduced to increase steric hindrance, thereby increasing the stable dispersibility of nano silicon dioxide in the system; on the other hand, when the coating agent is mixed with water, the introduced silane group may be hydrolyzed to produce Si-OH, which has a cross-linking effect with hydroxyl and carboxyl groups in the system, further increasing the cross-linking density of the system, thereby blocking water vapor and exerting excellent anti-corrosion performance.
[0022] In some embodiments of the present invention, the acrylic resin is methyl methacrylate-butadiene-styrene.
[0023] Another aspect of the present invention further provides a method for preparing a powdered cold-drawn polymer coating agent, comprising the following steps:
[0024] The modified graphite and molybdenum disulfide are mixed, a silane coupling agent is added, the mixture is stirred, polyethylene glycol, silicate, modified nano silicon dioxide, acrylic resin and dispersant are added, and a cross-linking agent is added, and a powdered cold-drawn polymer coating agent is obtained after homogeneous dispersion, drying and crushing.
[0025] In another aspect, the present invention also provides an application method of a powdered cold-drawn polymer coating agent, comprising the following steps:
[0026] Based on 100% by weight, raise the temperature to 75-85°C while stirring, add 18-20% of the powdered cold-drawn polymer coating agent into a tank containing excess water, continue stirring until the foam disappears, and then soak the material to be treated in the tank, keep the temperature at 65-85°C, and treat for 3-5 minutes.
[0027] Preferably, the material to be processed is a rust-free and scale-free seamless steel pipe, wire rod, steel strand or rolled steel pipe.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The powdered polymer coating agent provided by the present invention is environmentally friendly and has good adhesion, excellent lubrication performance and corrosion resistance, and is suitable for the application of dry drawing of various seamless steel pipes, wire rods, steel strands and oil drawing of rolled steel pipes.
[0030] (2) The present invention introduces stearic acid to modify the composite graphite, thereby first reducing the agglomeration phenomenon that is easily caused by its surface energy, increasing its compatibility in the system, and further improving the dispersion stability of the composite graphite in the system; at the same time, a slip-like phenomenon may exist between the spherical graphite and the natural flake graphite, which further improves the lubrication performance of the system under the synergistic effect of adsorption and friction with the molybdenum disulfide in the system.
[0031] (3) The present invention modifies nano-silica. On the one hand, long chain segments are introduced to increase steric hindrance, thereby increasing the stable dispersibility of nano-silica in the system; on the other hand, when the coating agent is mixed with water, the introduced silane groups may be hydrolyzed to produce Si-OH, which reacts with hydroxyl and carboxyl groups in the system to further increase the cross-linking density of the system, thereby blocking water vapor and exerting excellent anti-corrosion performance. DETAILED DESCRIPTION
[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0033] Unless otherwise specified, the reagents used below can be easily obtained from commercial companies. Natural flake graphite (particle size of 50 μm) and spherical graphite (particle size of 20 μm) were purchased from Lingshou County Malin Mineral Products Processing Factory.
[0034] Unless otherwise specified, the post-processing steps such as "ultrasonic dispersion", "reduced pressure distillation", "drying", "homogeneous dispersion" and "crushing" used below are routine operations for those skilled in the art and can be selected according to actual operations.
[0035] Unless otherwise specified, the polyethylene glycol used below is PEG400, the silane coupling agent is KH550, the acrylic resin is methyl methacrylate-butadiene-styrene (purchased from Shanghai Langqi Plastic Raw Materials Co., Ltd.), the silicate is sodium silicate monohydrate, the cross-linking agent is N,N-methylenebisacrylamide, the dispersant is sodium dodecyl sulfate, and the particle size of nano-silica is 20 nm.
[0036] Preparation Example 1
[0037] The preparation steps of modified graphite are as follows:
[0038] 10 g of composite graphite (natural flake graphite and spherical graphite mixed in a mass ratio of 1:0.4) was ultrasonically dispersed in 100 mL of petroleum ether, and 2 g of stearic acid was added. After continuing ultrasonic dispersion for 1.5 hours, the petroleum ether was removed by reduced pressure distillation to obtain modified graphite.
[0039] Preparation Example 2
[0040] The preparation steps of modified graphite are the same as those in Preparation Example 1, except that the amount of stearic acid added is 3.5 g.
[0041] Preparation Example 3
[0042] The preparation steps of modified graphite are the same as those of Preparation Example 1, except that the composite graphite is obtained by mixing natural flake graphite and spherical graphite in a mass ratio of 1:0.6.
[0043] Preparation Example 4
[0044] The preparation steps of modified graphite are the same as those of Preparation Example 1, except that 10 g of natural flake graphite is used to replace the composite graphite.
[0045] Preparation Example 5
[0046] The preparation steps of modified nano-silica are as follows:
[0047] Mix 10g of nano-silica and 50mL of deionized water, disperse by ultrasonication for 25min, heat to 60°C, add 4g of 1H,1H,2H,2H-perfluorooctyltriethoxysilane under stirring, then add 0.5mL of acetic acid, continue to heat to 75°C, stir and react for 2h, and dry to constant weight to obtain modified nano-silica.
[0048] Preparation Example 6
[0049] The preparation steps of modified nano-silica are the same as those in Preparation Example 5, except that the amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane added is 5.5 g.
[0050] Example 1
[0051] A powder type cold drawn polymer coating agent comprises the following raw materials in parts by weight: 3.5 parts of modified graphite, 2 parts of molybdenum disulfide, 6 parts of polyethylene glycol, 3.5 parts of silane coupling agent, 65 parts of acrylic resin, 3 parts of silicate, 1.5 parts of modified nano silicon dioxide, 5.5 parts of crosslinking agent and 2 parts of dispersant.
[0052] The preparation method of the powder type cold drawn polymer coating agent of this embodiment comprises the following steps:
[0053] The modified graphite and molybdenum disulfide are mixed, a silane coupling agent is added, the mixture is stirred, polyethylene glycol, silicate, modified nano silicon dioxide, acrylic resin and dispersant are added, and a cross-linking agent is added, and a powdered cold-drawn polymer coating agent is obtained after homogeneous dispersion, drying and crushing.
[0054] The modified graphite used in this example is obtained from Preparation Example 1, and the modified nano-silicon dioxide used is obtained from Preparation Example 5.
[0055] Example 2
[0056] A powder type cold drawn polymer coating agent comprises the following raw materials in parts by weight: 2 parts of modified graphite, 1 part of molybdenum disulfide, 2 parts of polyethylene glycol, 1 part of silane coupling agent, 50 parts of acrylic resin, 1 part of silicate, 1 part of modified nano silicon dioxide, 1 part of cross-linking agent and 1 part of dispersant.
[0057] The preparation method of the powder type cold drawn polymer coating agent in this embodiment has the same specific steps as in Example 1.
[0058] The modified graphite used in this example is obtained from Preparation Example 1, and the modified nano-silicon dioxide used is obtained from Preparation Example 5.
[0059] Example 3
[0060] A powder type cold drawn polymer coating agent comprises the following raw materials in parts by weight: 5 parts of modified graphite, 3 parts of molybdenum disulfide, 10 parts of polyethylene glycol, 6 parts of silane coupling agent, 80 parts of acrylic resin, 5 parts of silicate, 2 parts of modified nano silicon dioxide, 10 parts of cross-linking agent and 3 parts of dispersant.
[0061] The preparation method of the powder type cold drawn polymer coating agent in this embodiment has the same specific steps as in Example 1.
[0062] The modified graphite used in this example is obtained from Preparation Example 1, and the modified nano-silicon dioxide used is obtained from Preparation Example 5.
[0063] Example 4
[0064] A powder type cold drawn polymer coating agent and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the modified graphite is obtained from Preparation Example 2.
[0065] Example 5
[0066] A powder type cold drawn polymer coating agent and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the modified graphite is obtained from Preparation Example 3.
[0067] Example 6
[0068] A powder type cold drawn polymer coating agent and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the modified graphite is obtained from Preparation Example 4.
[0069] Example 7
[0070] A powdery cold-drawn polymer coating agent and a preparation method thereof. The specific implementation method is the same as Example 1, except that the modified nano-silica is obtained from Preparation Example 6.
[0071] Comparative Example 1
[0072] A powder type cold drawn polymer coating agent and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that composite graphite (natural flake graphite and spherical graphite mixed in a mass ratio of 1:0.4) is used to replace modified graphite in equal amounts.
[0073] Comparative Example 2
[0074] A powder type cold drawn polymer coating agent and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that an equal amount of nano silicon dioxide is used to replace modified nano silicon dioxide.
[0075] Performance Testing:
[0076] The coating agents prepared in the above Examples 1-7 and Comparative Examples 1-2 were subjected to the following performance tests. The specific test results are shown in Table 1:
[0077] (1) Adhesion performance: Based on 100% by weight, under stirring, the temperature was raised to 80°C, 19% of the powdered cold-drawn polymer coating agent was added to the tank containing the remaining water, and the stirring was continued until the foam disappeared. Then, the rust-free and oxide-free seamless steel pipe was immersed in the tank, and the temperature was maintained at 75°C. The treatment lasted for 4 minutes, and the samples were obtained. The adhesion test was carried out according to the standard GB / T1720-1989;
[0078] (2) Corrosion resistance: Based on 100% by weight, the temperature was raised to 80°C under stirring, and 19% of the powdered cold-drawn polymer coating agent was added to the tank containing the remaining water. The mixture was stirred until the foam disappeared, and then the rust-free and oxide-free seamless steel pipe was immersed in the tank at a temperature of 75°C for 4 minutes. The samples were then subjected to corrosion resistance tests according to GB / T6807-1991.
[0079] (3) Lubrication performance: The saponification value of each coating agent was measured to characterize its lubrication performance. The higher the saponification value, the higher the lubricity.
[0080] Table 1
[0081]
[0082] It can be seen from Table 1 that the coating agents provided by Examples 1 to 3 of the present invention have strong adhesion, high corrosion resistance and good lubrication performance.
[0083] By comparing Example 4 with Example 1, it can be seen that when the amount of stearic acid added to prepare the modified graphite is changed, the adhesion, corrosion resistance and lubricity of the coating agent are all reduced to a certain extent due to the agglomeration phenomenon easily induced by the surface energy of the composite graphite.
[0084] By comparing Example 5 and Example 6 with Example 1, it can be seen that when the ratio and type of natural flake graphite and spherical graphite are changed respectively when preparing modified graphite, the binding effect of natural flake graphite and spherical graphite in the composite graphite is affected, and the possible slip-like effect between them is weakened, which in turn leads to a weakening of the synergistic effect between it and molybdenum disulfide in the system, which has a great influence on the corrosion resistance and lubrication properties of the coating agent.
[0085] By comparing Example 7 with Example 1, it can be seen that when the amount of 1H,1H,2H,2H-perfluorooctyltriethoxysilane added is changed when modifying nano-silica, the stability of the system may be affected, thereby causing the adhesion, corrosion resistance and lubricity of the coating agent to decrease.
[0086] By comparing Comparative Example 1 with Example 1, it can be seen that when unmodified composite graphite is directly added, the adhesion, corrosion resistance and lubricity of the coating agent will decrease, which is caused by the unsatisfactory synergy between the components of the system.
[0087] From the comparison between Comparative Example 2 and Example 1, it can be seen that when unmodified nano-silicon dioxide is directly added, its dispersibility in the system will drop sharply, which will further reduce the modification effect of the system after the addition of nano-silicon dioxide, affecting the overall performance of the system.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A powder type cold drawn polymer coating agent, characterized in that: The polymer coating agent comprises the following raw materials in parts by weight: 2 to 5 parts of modified graphite, 1 to 3 parts of molybdenum disulfide, 2 to 10 parts of polyethylene glycol, 1 to 6 parts of silane coupling agent, 50 to 80 parts of acrylic resin, 1 to 5 parts of silicate, 1 to 2 parts of modified nano silicon dioxide, 1 to 10 parts of crosslinking agent and 1 to 3 parts of dispersant.
2. The powder type cold drawn polymer coating agent according to claim 1, characterized in that: The preparation steps of the modified graphite are as follows: The composite graphite is dispersed in an organic solvent by ultrasonic method, and then stearic acid is added. After the ultrasonic dispersion is continued for 1 to 2 hours, the organic solvent is removed by vacuum distillation to obtain the modified graphite.
3. The powdery cold-drawn polymer coating agent according to claim 2, characterized in that: The composite graphite is a mixture of natural flake graphite and spherical graphite.
4. The powder type cold drawn polymer coating agent according to claim 2, characterized in that: The mass ratio of the composite graphite to stearic acid is 1:(0.1-0.3).
5. The powder type cold drawn polymer coating agent according to claim 1, characterized in that: The acrylic resin is methyl methacrylate-butadiene-styrene.
6. The powder type cold drawn polymer coating agent according to claim 1, characterized in that: The preparation steps of the modified nano silicon dioxide are as follows: The nano-silica and deionized water are mixed, ultrasonically dispersed for 20 to 30 minutes, heated to 55 to 70° C., 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is added under stirring, and then acetic acid is added, and the temperature is continued to be raised to 70 to 80° C., stirred for reaction for 1 to 3 hours, and dried to obtain the modified nano-silica.
7. The powdery cold-drawn polymer coating agent according to claim 6, characterized in that: The mass ratio of the nano silicon dioxide to 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 1:(0.3-0.5).
8. The powdery cold-drawn polymer coating agent according to claim 6, characterized in that: The particle size of the nano silicon dioxide is 10 to 30 nm.
9. A method for preparing the powdery cold-drawn polymer coating agent according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified graphite and molybdenum disulfide are mixed, a silane coupling agent is added, the mixture is stirred, polyethylene glycol, silicate, modified nano silicon dioxide, acrylic resin and dispersant are added, and a cross-linking agent is added, and a powdered cold-drawn polymer coating agent is obtained after homogeneous dispersion, drying and crushing.
10. Use of the powdery cold-drawn polymer coating agent according to any one of claims 1 to 8 or the powdery cold-drawn polymer coating agent obtained by the preparation method according to claim 9, characterized in that: The following steps are involved: Based on 100% by weight, raise the temperature to 75-85°C while stirring, add 18-20% of the powdered cold-drawn polymer coating agent into a tank containing excess water, continue stirring until the foam disappears, and then soak the material to be treated in the tank, keep the temperature at 65-85°C, and treat for 3-5 minutes.
Citation Information
Patent Citations
An environmentally friendly lubricating coating agent for cold-drawn steel wire, its preparation method and application
CN113399483B
Cited By
Titanium alloy high-temperature drawing composite coating agent based on interface bonding reinforced phase as well as preparation method and application of titanium alloy high-temperature drawing composite coating agent
CN121874766A